الصيغ الزمنية للفعل ودلالاتها في المنام الكبير للوهراني - عبد القادر, مغدير (جامعة الوادي - University of Eloued, 2022)
يستهدف هذا المقال دراسة الصيغ الزمنية للفعل في المنام الكبير للوهراني للوقوف على وظيفته في تلوين الأحداث بأبعاد زمنية مختلفة، ودلالات سياقية متنوعة، ويحاول الإجابة عن الأسئلة الآتية: كيف تجلى الزمن في المنام الكبير؟ وإلى أي مدى وفق الوهراني في توظيفه؟ وما هي الدلالات التي حملتها الأفعال في المنام الكبير؟ للأجابة عن هذه الأسئلة اتبع الباحث المنهج الوصفي التحليلي، فأحصى الأفعال بأزمنتها الثلاثة، ثم عاد إلى سياقاتها، وحللها للوصول إلى دلالاتها السياقية ، ووجد أن لكل زمنٍ منها أزمنة متعددة ودقيقة، فالماضي قد يكون للقريب والبعيد، والمضارع قد يدل على الماضي أو الحاضر أو المستقبل، والذي يتحكم في ذلك ليست صيغة الفعل، وإنما القرائن اللفظية والحالية المصاحبة للفعل. This article aims to study the verb tense the big dream of Al-Wahrani, to find out his way in shed light on the events with different time dimensions and various contextual. He tries to answer these questions: How did tense manifest in the big dream? And to what extent did Al-Wahrani succeed to employ it? And what are the indications carried by the verbs in the big dream? To answer these questions, the researcher followed the descriptive and analytical approach, through which he counted the verbs by their three tenses, then he returned to contexts and tried to interrogate and analyze them to reach their various contextual implications, and found that each tense has multiple and accurate tenses, the past may be both near and far. and the present may denote the present itself as well as the past and the future . And which controls all of this, is not the verb form, but rather the verbal and current clues which accompanied the verb.
مقال
Keywords: الزمن، الفعل، الدلالة، الماضي، الحاضر، المستقبل; Tense, Verb, Signification, Past, present , Future . key words